Cervical schistosomiasis. Issue 6 (1st November 2001) - Sharma, S.; Boyle, D.; Wansbrough-Jones, M. H.; Chiodini, P. L.; Smith, J. R.
Abstract : We present a case history of a woman who was diagnosed as having cervical schistosomiasis on histology following investigations for abnormal cervical smear. Schistosomiasis of the female genital tract can present with varied symptoms and there is a need for greater awareness of this diagnosis as the number of travellers to schistosomiasis-endemic areas rises. Travellers to these areas should be warned about the risk of swimming in lakes and rivers.